INTERFERENSI DAN INTEGRASI BAHASA DALAM DIALOG FILM MELODYLAN (KAJIAN SOSIOLINGUISTIK) - Aria Bayu Setiaji; Ijriah Musaali (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
Abstract This research aims to find out whether in the film "Melodylan" there is interference in the fields of phonology, morphology, syntax and semantics and to analyze the use of language integration. This research uses a descriptive-qualitative method to analyze the dialogue in the film "Melodylan". The data source in this research is the dialogue in the film Melodylan. Data collection was carried out using the skill-free listening (SBLC) technique. The data analysis techniques used are data reduction, data presentation, as well as drawing conclusions and verification. The results of this research are (1) the use of phonological interference in 10 utterances. (2) use of morphological interference in 8 utterances, (3) use of syntactic interference in 5 utterances, and use of semantic interference in 7 utterances. Furthermore, language integration was found in 19 utterances. Based on the results of this research, it can be concluded that in the dialogue of the film "Melodylan" there is a lot of interference in the field of phonology with a total of 10 utterances, and there is a lot of integration of foreign languages that have become Indonesian, namely 19 utterances. Therefore, the author provides suggestions to avoid the use of language integration in everyday life, language users should always prioritize Indonesian wherever they are. Keywords: Sociolinguistics, Interference, Integration, film dialogue